If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(h-4)=-0.5(36-10h)
We move all terms to the left:
3(h-4)-(-0.5(36-10h))=0
We add all the numbers together, and all the variables
3(h-4)-(-0.5(-10h+36))=0
We multiply parentheses
3h-(-0.5(-10h+36))-12=0
We calculate terms in parentheses: -(-0.5(-10h+36)), so:We get rid of parentheses
-0.5(-10h+36)
We multiply parentheses
5h-18
Back to the equation:
-(5h-18)
3h-5h+18-12=0
We add all the numbers together, and all the variables
-2h+6=0
We move all terms containing h to the left, all other terms to the right
-2h=-6
h=-6/-2
h=+3
| 7x+3=5x+7=10 | | (7x+3)(5x+7)=10 | | -5=a/20 | | 2/5y+19=30 | | 3s–70=s | | 2y+33=4y-68+3y-42 | | 81+75+x=180 | | 6-2(x-1)=9x+4 | | (7x+13)(5x+7)=10 | | 2y=5,4y=15 | | -16s+15s-12s=13 | | -63=7k | | 29=-8+v/3 | | -72(x-14)=-4 | | 56=8y=-96 | | 26=3x+7x+6 | | 4.4+5.5=x | | 2y+33+4y-68=3y-42 | | 144=8-8x | | 3y–42=2y+33+4y-68 | | 2-3(4x+5)=23 | | -49=v/2 | | 1+x=4567890 | | 5(6-y)=12.5 | | -6|5x-1|-5=-29 | | 0.5y-8=3(y+4) | | -2(4x-1)+3=-5x+11 | | 2t+15=9t-27 | | 9t–27=2t+15 | | 189=26-v | | 6(x-1)=8x-2(x+5) | | 3a-57=2a-33 |